2010
DOI: 10.1093/rheumatology/keq196
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-18 is a key mediator in dermatomyositis: potential contribution to development of interstitial lung disease

Abstract: Serum IL-18 was strikingly elevated in patients with DM and was associated particularly with disease activity and ILD complication in DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
37
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 11 publications
5
37
1
1
Order By: Relevance
“…8,9 In our study, serum IL-18 level was found to be significantly elevated in patients with DM when compared to those with PM or healthy individuals. The level was particularly high in DM patients with severe disease, in agreement with a previous report by Gono et al 11 However, we did not observe any significant difference in IL-18 level between the PM and control groups. This finding differs from a previous study that demonstrated increased IL-18 in patients with PM.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…8,9 In our study, serum IL-18 level was found to be significantly elevated in patients with DM when compared to those with PM or healthy individuals. The level was particularly high in DM patients with severe disease, in agreement with a previous report by Gono et al 11 However, we did not observe any significant difference in IL-18 level between the PM and control groups. This finding differs from a previous study that demonstrated increased IL-18 in patients with PM.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with a previous study that also found no difference in serum IL-18 in PM patients with or without accompanying ILD. 11 Our results suggest that IL-18 plays greater roles in the induction of ILD in DM when compared to PM patients, and IL-18 can be used as a serum marker for DM patients with ILD.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Furthermore, IL-18 serum levels were found to be increased in DM patients and to decline as patients approached clinical remission [18]. A recent study showed that IL-18 serum levels are higher in DM patients with interstitial lung disease than those without it, and that IL-18, ferritin, and creatine kinase are all correlated [19]. Serum IL-18 levels were significantly higher in DM than in PM patients.…”
Section: Interleukin-18mentioning
confidence: 98%
“…Serum IL-18 levels were significantly higher in DM than in PM patients. The authors suggested that IL-18 may stimulate type 1 IFN-regulated chemokines and pDCs, which induce muscle inflammation in DM [19].…”
Section: Interleukin-18mentioning
confidence: 99%